Editorial: Towards leaner and more effective value chain development - Donovan, J.; Stoian, D.; Ferries, S. (Practical Action Publishing, 2017)
Value chain development (VCD) is a common term in today’s development lexicon1, where its use tends to conjure passionate ideas about how development programming can support smallholder participation in growing markets in the interest of economic growth, job creation, gender empowerment, and sustainable use of natural resources, among other goals. Since the early 2000s, Enterprise Development and Microfinance (EDM) has featured considerable debate on how to design market-oriented development interventions with smallholders, often based on positive experiences by a given NGO or project in a particular context. Early articles helped to put VCD on the development agenda, while advancing innovation in market-based project design and implementation. However, after more than a decade of it being firmly placed on the agenda, we still know relatively little about VCD. Apart from isolated case studies, the question of whether VCD has lived up to the expectations of smallholders, of the private sector, and of development agencies remains an open one. This double edition of EDM addresses the design, implementation, and impact of VCD support to smallholders and to small and medium enterprises (SMEs) as an important, yet under-researched dimension of VCD. The eight articles look into the needs and opportunities for increasing the effectiveness of VCD support services, with discussions on: the role of NGOs or governments in VCD; how large-scale buyers and certification programs shape VCD; and the role of finance and impact bonds in VCD. Advancing ideas on how to get the right mix of services, at the right time, to the right people, taking into account variations in the context in which livelihoods and business activities are embedded, will help stakeholders to effectively deliver on poverty and broader development goals.